Metabolomic and microbiomic insights into color changes during the sweating process in Dipsacus asper - He, Hua; Xu, Jiao; Zhou, Taimin; Yang, Yang; Yang, Changgui; Xiao, Chenghong; Zhang, Chenggang; Li, Liangyuan; Zhou, Tao (Frontiers in Microbiology, 2023)
Sweating is one of the most important primary processing methods of Chinese medicinal materials. Dipsacus asper is a typical representative of sweating treatment that is recommended by the Chinese Pharmacopoeia. The color change of the fracture surface of the root is the prominent feature of sweating treatment. However, few studies have focused on the mechanism of color change during sweating treatment. In this study, widely targeted metabolomics and ITS high-throughput sequencing technologies were applied to detect metabolites and microbial structure and diversity in the root of D. asper during sweating treatment. A total of 667 metabolites, including 36 downregulated and 78 upregulated metabolites, were identified in D. asper following sweating treatment. The significantly differential metabolites were divided into 12 classes, including terpenoids and phenolic acids. Moreover, all the differential terpenoids were upregulated and 20 phenolic acids showed a significant change after sweating treatment. In addition, microbial community diversity and richness increased following sweating treatment. The composition of microbial communities revealed that the relative abundances of Ascomycota and Basidiomycota significantly changed after sweating treatment. Correlation analysis revealed that Ascomycota (Fusarium sp., Macrophomina sp., Ilyonectria sp., Memnoniella sp., Penicillium sp., Cyphellophora sp., Neocosmospora sp., unclassified_f_Nectriaceae, and unclassified_o_Saccharomycetales) and Basidiomycota (Armillaria sp.) were associated with the content of terpenoids (6-deoxycatalpol and laciniatoside III) and phenolic acids (3-(4-hydroxyphenyl)-propionic acid, ethyl caffeate, 4-O-glucosyl-4-hydroxybenzoic acid, 2-acetyl-3-hydroxyphenyl−1-O-glucoside, 4-O-glucosyl-3,4-dihydroxybenzyl alcohol, 3-O-feruloylquinic acid, 3,4-O-dicaffeoylquinic acid methyl ester, O-anisic acid, and coniferyl alcohol). We speculate that the Ascomycota and Basidiomycota affect the content of terpenoids and phenolic acids, resulting in color change during sweating treatment in D. asper. This study provides a foundation for analyzing the mechanism involved in the processing of Chinese medicinal materials.